Incorporation of High Volume Ground Granulated Slag From Blast Furnaces in Pavement Quality Concrete - Patel, Vikram J.; Juremalani, Jayesh; Kumavat, Hemraj R. (Engineering, Technology & Applied Science Research, 2024)
Supplementary cementitious materials (SCMs) are commonly introduced into the concrete mix to increase their properties, addressing the current need for durable and robust pavements. With every ton of Ordinary Portland Cement (OPC) produced through processes such as fossil fuel combustion and limestone fermentation, carbon dioxide is released into the atmosphere. Conversely, Ground Granulated Blast-furnace Slag (GGBS), being abundantly available, presents a viable more environmentally friendly alternative to cement for various concrete applications. This work studies the influence of GGBS, in combination with chemical admixtures, on M40 grade binary blended concrete mixtures. The aim of the study was to improve the strength characteristics at various stages of concrete curing. The results indicated that the GGBS-incorporated concretes (replacing 60%, 65%, and 70% of the cement) exhibited an increase in compressive strength after prolonged curing. The average density of fresh concrete mixes containing GGBS did not exhibited a noticeable increase. A marginal disparity in air content was observed in the replacement mix. Minimal length changes were observed in the drying shrinkage test after a curing duration of 360 days compared to conventional concrete mixtures.